Estudo de Novos Atraentes de Oviposição de Fêmeas do Mosquito Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Paulino, Sivaldo Soares (2008)
Mosquito-borne viral tropical diseases represent a great threat to the global public health. Diseases transmitted by mosquitoes are usually endemic, and millions of people throughout the world are infected by mosquitoes of the Family Culicidae. The mosquito Aedes (Stegomyia) aegypti (Linnaeus, 1762) (Diptera: Culicidae) is the main vector of the dengue viruses and the urban yellow fever. The great proliferation of the different mosquitoes species is not only due to the high number of the breeding sites in the urban areas, but also due to the development of the resistance of the mosquitoes to the insecticide, such as the chlorinated organic compounds, organophosphates, carbamates, as well as the biological insecticide. With respect to the environment, the Laboratory of Synthesis and Isolation of the Pheromones (LaSIF) has been studying in the last years more ecological alternatives of control and surveillance of mosquito-borne vector of tropical diseases. Therefore, studies related to the breeding sites of the mosquito Ae. aegypti were accomplished as a form of obtaining data on how to control the populations of this vector. A study of the selection of specific oviposition breeding sites of the Ae. aegypti female mosquito was accomplished with different aqueous samples collected from artificial and natural breeding sites. Among all the different aqueous samples studied at the laboratory, the Aloe vera (Liliaceae) infusion was considered greater stimulant of the oviposition behavior of the Ae. Aegypti female. The Aloe vera infusion was also bioassayed the field and compared with the traditional attractive infusion used in programs of control and surveillance of the mosquito Ae. aegypti. Sample preparation methods solid phase extraction (SPE), stir-bar sorptive extration (SBSE), and liquid-liquid extraction (LLE), were accomplished to isolate the organic compounds present in the Aloe vera infusion. The extracts obtained by the extraction techniques were analyzed in relation to the stimulating potential of oviposition behavior of the female of the mosquito Ae. Aegypti. The separation of the organic substances contained in the extracts was accomplished through gas chromatography (GC). The identification of isolated substances was accomplished through to the use of high resolution gas chromatography coupled the mass spectrometry (CG-MS), and the active components in the extracts were located by coupled high resolution gas chromatography-electrophysiology (GC-EAG).